Effect of Nozzle Travel Path Strategies on the Mechanical Properties of Inconel 625 Superalloy Parts Formed by Direct Laser Metal Deposition - Duong, Van Nguy; Trinh, Quang Hung; Doan, Tat Khoa (JST: Engineering And Technology For Sustainable Development, 2023)
To reduce the occurrence of cracks in the Inconel 625 nickel-based super-alloy during the Direct Laser Metal Deposition (DLMD) process, this study simulated the temperature and stress fields of thin-walled parts. The model was used to determine the effect of nozzle travel path strategies (single direction and reverse direction) on the final stress distribution, and compared the differences in residual stress distribution within the thin-walled part. The results showed that with the single direction scanning method, the residual stress at both ends of the thin-walled part was relatively high while the stress at the middle was smaller, with a stress difference between the maximum and minimum of about 900 MPa. In contrast, with the reverse direction scanning method, the residual stress in the thin-walled part was distributed relatively evenly, with a stress difference of about 300 MPa between both ends and the center. The experimental results showed that with the single direction scanning method, cracks occurred at both ends and in the middle of the thin-walled part, whereas with the reverse direction scanning method, warping and cracks phenomena were eliminated. The microstructure of the Inconel 625 in the forming layer is characterized by a columnar crystal structure that has a small length and grows perpendicularly to the scanning direction. This growth is continuous between the forming layers. In both cases, the micro-hardness increases with the height of the formed layers; the microhardness values in the left, right, and middle regions are relatively uniform, the microhardness measurement values range from 420 to 450 HV.